Analysis of the Influence of Effective Leadership and Organizational Leadership on Organizational Citizenship Behavior with Job Satisfaction as a Mediation - Kurniawati, Rina; Kirana, Kusuma Chandra; Subiyanto, Didik (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This research is motivated by the importance of organizational justice and effective leadership in shaping job satisfaction and organizational citizenship behavior (OCB) in the police environment. The purpose of this study is to analyze the influence of organizational justice and effective leadership on OCB with job satisfaction as a mediating variable in Sleman Police Traffic Division personnel. The research method used is a quantitative approach with the type of survey research. The research sample amounted to 170 respondents who were members of the Traffic Division of the Sleman Police. The data was collected through the distribution of questionnaires, while the analysis tool used was Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with the help of SmartPLS software. The results of the study show that organizational fairness has a positive and significant effect on job satisfaction and OCB, while effective leadership also has a significant effect on job satisfaction and OCB. In addition, job satisfaction has been shown to be a mediating variable that strengthens the relationship between organizational fairness and effective leadership with OCB. Although the majority of respondents had a positive perception, there are still aspects that need to be improved, especially related to procedural consistency, appreciation from leaders, and members' opportunities to convey ideas and develop careers.